Donut‐Shaped Li4Ti5O12 Structures as a High Performance Anode Material for Lithium Ion Batteries. Issue 3 (28th August 2014) - Haridas, Anulekha K.; Sharma, Chandra S.; Rao, Tata N.
<x xml:space="preserve">Abstract</x> Lithium titanate (LTO) spinel 3D porous sub‐micrometer donuts synthesized by combined sol‐gel and electrospraying reveal a wall thickness of 200–250 nm with grain sizes in the range of 60–100 nm. Electrochemical testing of sub‐micrometer donuts in half‐cell mode exhibited a reversible specific capacity of 141 mAh/g even after 200 cycles of charging and discharging at 1C rate. The LTO structures with nanograins effectively reduce the Li ion diffusion path length, providing easy charge and discharge with good cyclability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>